Influence of wetting–drying cycles on swell–shrink behaviour of GPA-reinforced expansive clay beds. Issue 3 (2nd July 2020) - Phanikumar, B. R.; Muthukumar, M.
ABSTRACT: Granular pile-anchor (GPA) technique is an innovative tension-resistant foundation technique which can effectively ward off the dual swell–shrink problem posed by expansive clays. The other tension-resistant foundation techniques are drilled piers, belled piers and under-reamed piles. Laboratory scale model studies and field scale experiments on GPAs revealed that swelling of expansive clay beds could be effectively controlled by GPA technique. This paper presents results obtained from laboratory scale model studies on GPA-reinforced expansive clay beds subjected to alternate cycles of wetting and drying. Swelling and shrinkage of the clay beds were monitored for three wetting–drying cycles ( N ) spanning a time period of 300 days. The clay beds were reinforced with varying number of GPAs ( n = 0, 1, 2 and 3). Swelling (mm) and shrinkage (mm) of the clay beds in a given wetting–drying cycle decreased with increasing number of GPAs. Further, swelling (mm) and shrinkage (mm) significantly decreased with increasing number of wetting–drying cycles ( N ) also. For a given number of GPAs ( n ), swelling and shrinkage decreased with increase in depth from the top of the clay bed too.